Analisis Risiko K3 Menggunakan Metode AS/NZS 4360 2004 dan HIRARC Pada proyek Kontruksi - Mohamad Agus Dwi Kurniawan; Sony Susanto; Fitry Rahmawati (Institut Teknologi Garut, 2025)
The Occupational Health and Safety (OHS) practices in the Mrican Roya Cluster construction project by PT BJS Property were carried out using a descriptive quantitative approach and risk analysis based on the AS/NZS 4360:2004 standard. Data were collected through questionnaires distributed to 70 respondents from various positions, including directors, foremen, masons, and field workers. The collected data were analyzed using validity and reliability tests with the aid of IBM SPSS Statistics software to ensure the accuracy of the research instruments. Subsequently, risks were assessed using a combination of probability and severity scores classified within a risk matrix. The analysis results revealed that out of 12 risk items identified through hazard identification, 3 were categorized as high, 8 as medium, and 1 as low. The highest risks included falling from heights, being struck by heavy materials, and physical fatigue. The main contribution of this analysis is the provision of a risk prioritization map that can serve as a basis for decision-making in more targeted accident prevention and mitigation strategies. Following mitigation measures such as OHS training, the use of personal protective equipment (PPE), strict supervision, and evaluation of work procedures, risk levels decreased, with most high-risk items shifting to medium risk. The study concludes that implementing OHS risk management using the AS/NZS method and HIRARC in a planned, measurable, and sustainable manner is highly effective in reducing accident potential while simultaneously improving productivity in construction projects. These findings have significant practical implications, as the applied risk assessment method can be adapted for other construction projects, thereby helping companies create safer and more efficient work environments across different scales of development.